Social Media Use and Quality of Sleep among Undergraduate Nursing Students in Kathmandu - Bhattarai, Tilarupa; Upadhyay, Radhika; KC, Tulza; Shahi, Bhawani; Sharma, Muna (Journal of Institute of Medicine Nepal, 2024)
Introduction Now-a-days, social media use has increased, which has its own benefits and limitations including its adverse effects on an individual's sleep. The objective of study was to find-out social media use patterns in terms of its addiction level and quality of sleep of nursing students. Methods Cross sectional design was used including 565 B.Sc. Nursing students at six nursing campuses in Kathmandu district. The data collection tool consisted of questions related to socio-demographic information; social media use behavior, Social Media Addiction Scale developed by Cengiz Şahin and Pittsburgh Sleep Quality Index, developed by Buysse. After taking administrative approval from the respective colleges and informed consents from the respondents, data was collected using self-administered questionnaires. Data was entered in SPSS Version 16 and analyzed using descriptive and inferential statistics. Results All respondents were female with mean age of 21.37 years; 72.9% of respondents had good quality of sleep, 59.5% had medium level addiction to social media. Social media addiction and poor sleep quality was found to have positive correlation (r=0.51, p < 0.01). Conclusion The nursing students were addicted to social media; and some of them had poor sleep quality. The quality of sleep wass correlated with social media use. It is recommended that the students need to decrease their social media use engagement.